Financial Commitment to a Greener Future: Investigating Environmental Protection Spending and Its Impact on Sustainable Development Goals - Samsony Petrus Sinaga (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
This research examines the role of environmental protection expenditure (EPE) in advancing the Sustainable Development Goals (SDGs) within seven Asian countries: China, Indonesia, Israel, South Korea, Malaysia, the Philippines, and Thailand. Focusing on SDG 6 (Clean Water and Sanitation), SDG 11 (Sustainable Cities and Communities), SDG 12 (Responsible Consumption and Production), SDG 14 (Life Below Water), and SDG 15 (Life on Land), the research assesses the impact of financial commitments on sustainable development outcomes. Using panel data analysis, the study evaluates the relationship between EPE and the selected SDGs while controlling for economic growth, foreign direct investment (FDI), income inequality, and trade as a percentage of GDP. Results show that increased environmental spending significantly improves clean water access, urban sustainability, responsible consumption, marine conservation, and terrestrial biodiversity. Countries with robust environmental protection frameworks and higher investments in green technologies demonstrate better SDG performance. South Korea's Green New Deal and China's renewable energy investments serve as successful models of integrating economic growth with environmental sustainability. Conversely, Indonesia and the Philippines face challenges in enforcing environmental regulations, underscoring the need for stronger governance. The study highlights the importance of strategic financial commitments to environmental protection in driving sustainable development. It provides insights for policymakers, businesses, and international organizations aiming to align economic activities with sustainability goals. Emphasizing effective governance, innovative financing, and public-private partnerships, the research contributes to the discourse on achieving a greener future for Asia